Analisis Yuridis Proses Penyidikan Tindak Pidana Terorisme menurut Hukum di Indonesia: Analisis Teori Hukum Positif dan Teori Hukum Responsif - Raja Zailani; Idham Idham; Erniyanti Erniyanti (Kajian Ilmiah Hukum dan Kenegaraan, 2022)
Purpose: The purpose of writing this journal is to find out the legal arrangements for investigating criminal acts of terrorism according to Indonesian law, and to find out the obstacles and efforts to investigate criminal acts of terrorism according to Indonesian law. Method: The method used is a normative approach, namely through library research, and an empirical approach, namely through field research by conducting a series of interviews with respondents and informants to obtain field data. Result: The results of the study show that the legal arrangements for investigating criminal acts of terrorism according to Indonesian law, namely that criminal acts are strictly and specifically regulated in the Terrorism Law and are also regulated in general by the Criminal Code, however, the investigation process is not specifically regulated in the Terrorist Law. Therefore, the procedural law, starting from the investigation process to the decision of the Court, is still regulated in the Criminal Procedure Code. Obstacles to investigating terrorism crimes according to law in Indonesia are that investigators always have difficulties in finding initial evidence, examining perpetrators who feel they are in the right position, perpetrators are suspected of having psychiatric disorders, low education of perpetrators, and the attitude of perpetrators of criminal acts of terrorism who insist not commit acts of terrorism. Conclusion: The implementation efforts that can be made are that the investigator continues to detain and confiscate evidence, the investigator asks for help from doctors for perpetrators who are mentally ill, the investigator carries out extensive interpretations by expanding the meaning of the words contained in the Terrorism Law against perpetrators with low education.